From the taste to potyguês: the transtemporal of language (Palíndromo, 2022)
If language is fascist because it forces people to say (BARTHES, 2013), are there other ways of using language? The language, here, is the one that says, that speaks, but it is also the one that tastes (the tongue) and manifests. We are talking (of) two languages ​​and a manifest against the erasure of many others. The official language of Brazil, Portuguese, a colonial mark that obliges us to say it like this: in Portuguese; the tongue of taste, the one that tastes and savours food; and, finally, the Potyguês presented by Juão Nyn (2020) as a manifesto of what is possible to create among them. The heart vowel “y” resumes a sacred sound erased by the official language at the time when culinary knowledge transformed into culinary flavours to communicate memories and reconnect us with the times of dreams. Either through the resumption of cosmogonies or through the evocation of memory, both propose other ways of (un)making language. For this recipe: ancestral knowledge, mouth, teeth and sound. The bites of a colonial past echo in other ways of doing and (sub)verting language.
Keywords: Taste; Potyguês; Language; The times of dreams